2017
DOI: 10.1177/1010428317695528
|View full text |Cite
|
Sign up to set email alerts
|

The novel CXCR4 antagonist, PRX177561, reduces tumor cell proliferation and accelerates cancer stem cell differentiation in glioblastoma preclinical models

Abstract: Glioblastoma is the most frequent and the most lethal primary brain tumor among adults. Standard of care is the association of radiotherapy with concomitant or adjuvant temozolomide. However, to date, recurrence is inevitable. The CXCL12/CXCR4 pathway is upregulated in the glioblastoma tumor microenvironment regulating tumor cell proliferation, local invasion, angiogenesis, and the efficacy of radio-chemotherapy. In this study, we evaluated the effects of the novel CXCR4 antagonist, PRX177561, in preclinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…Chia et al (2018) showed that, whilst CSF-1 played a role in macrophage recruitment, signalling to Cxcr4 was absolutely required for the recruitment of macrophages to the Akt-transformed brain in zebrafish tumour initiation, and that PNC-derived Cxcl12 was the major ligand for this interaction [142]. Cxcr4 signalling has been shown to promote progression of many cancers in mammals including glioblastoma, through both cancer cell autonomous signalling and leukocyte interactions [106,[176][177][178][179][180][181]. However, the pro-tumour effect of Cxcr4 signalling at the preneoplastic stage was macrophage specific [142].…”
Section: Chemokines Recruit Leukocytes To Pncsmentioning
confidence: 99%
“…Chia et al (2018) showed that, whilst CSF-1 played a role in macrophage recruitment, signalling to Cxcr4 was absolutely required for the recruitment of macrophages to the Akt-transformed brain in zebrafish tumour initiation, and that PNC-derived Cxcl12 was the major ligand for this interaction [142]. Cxcr4 signalling has been shown to promote progression of many cancers in mammals including glioblastoma, through both cancer cell autonomous signalling and leukocyte interactions [106,[176][177][178][179][180][181]. However, the pro-tumour effect of Cxcr4 signalling at the preneoplastic stage was macrophage specific [142].…”
Section: Chemokines Recruit Leukocytes To Pncsmentioning
confidence: 99%
“…This protein reduces the frequency of aldehyde dehydrogenase positivity among the cancerous cells which are the indicators of CSC function [52]. This data suggests that THTMP could not promote the dormancy of CSCs, in contrast, we could observe that the CXC chemokine receptor 4 signaling (CXCR4) is modulated by THTMP, which confirms its role in the wake-up therapeutic strategy in targeting CSCs [53,54].…”
Section: Discussionmentioning
confidence: 66%
“…A novel antagonist of CXCR4, a receptor for CXCL12 that increases in tumors, induced CSC differentiation and reduced tumor cell growth in a preclinical glioblastoma multiforme (GBM) model. 157 …”
Section: Strategies To Target Cscsmentioning
confidence: 99%